Does employment protection help immigrants? Evidence from European labor markets - Filipa Sá (Institute for the Study of Labor (IZA), 2008)
High levels of employment protection reduce hiring and firing and have a theoretically ambiguous effect on the employment level. Immigrants, being new to the labor market, may be less aware of employment protection regulations and less likely to claim their rights, which may create a gap between the costs for employers of hiring a native relative to hiring an immigrant. This paper tests that hypothesis drawing on evidence for the EU and on two natural experiments for Spain and Italy. The results suggest that strict employment protection legislation (EPL) gives immigrants a comparative advantage relative to natives. Stricter EPL is found to reduce employment and reduce hiring and firing rates for natives. By contrast, stricter EPL has no effect on most immigrants and may even increase employment rates for those who have been in the country for a longer time.
urn:nbn:de:101:1-2008032631
Keywords: J6; 330; Employment protection; immigration; Kündigungsschutz; Beschäftigungseffekt; Migranten; Asymmetrische Information; Arbeitsnachfrage; Kündigung; EU-Staaten; Spanien; Italien